Anomalies in the Cosmic Microwave Background and Their Non-Gaussian Origin in Loop Quantum Cosmology - Agullo, Ivan; Kranas, Dimitrios; Sreenath, V. (Frontiers in Astronomy and Space Sciences, 2021)
Anomalies in the cosmic microwave background (CMB) refer to features that have been observed, mostly at large angular scales, and which show some tension with the statistical predictions of the standard $Λ$CDM model. In this work, we focus our attention on power suppression, dipolar modulation, a preference for odd parity, and the tension in the lensing parameter $A_L$. Though the statistical significance of each individual anomaly is inconclusive, collectively they are significant, and could indicate new physics beyond the $Λ$CDM model. In this article, we present a brief, but pedagogical introduction to CMB anomalies and propose a common origin in the context of loop quantum cosmology.